2019
DOI: 10.5037/jomr.2019.10102
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Ridge Preservation after Tooth Extraction Using Different Bone Graft Materials and Autologous Platelet Concentrates: a Systematic Review

Abstract: Objectives To review and assess the efficiency of different post extraction socket preservation techniques. Material and Methods An electronic literature search was performed on the MEDLINE and Embase databases. The review included human studies published between from January 1 st , 2007 to January 1 st , 2018, in English. Outcome measures included dimensional changes and/or histological evaluation of alveolar bone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 60 publications
3
61
1
4
Order By: Relevance
“…The clearly defined dental alveolar compartment provides these conditions. DBM paste exhibits significantly higher bone formation than synthetic bone replacement materials, if applied in the alveolar ridge [ 25 ]. Also, in cases of vertebral body fusion, freshly dissected intervertebral space offers optimized, osteoinductive conditions [ 21 , 23 , 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clearly defined dental alveolar compartment provides these conditions. DBM paste exhibits significantly higher bone formation than synthetic bone replacement materials, if applied in the alveolar ridge [ 25 ]. Also, in cases of vertebral body fusion, freshly dissected intervertebral space offers optimized, osteoinductive conditions [ 21 , 23 , 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of successful applications are the support of osseointegration of dental implants, but also to support arthrodesis procedures on joints. Even in human spine surgery the results were promising [ 22 , 23 , 24 , 25 , 26 , 27 ]. But clinical application in large bone defect is rare and mainly restricted to experimental approaches since DBM is easy to place in the bony gap, but a challenge to keep it there.…”
Section: Introductionmentioning
confidence: 99%
“…3 A recent study 4 found that there was a higher mean percent vital bone when no grafting was completed and that no one bone substitute was superior to another, but considerable loss of ridge height and width accompanies a non-grafted extraction socket. [1][2][3]5,6 A goal of ridge preservation is to maintain the overall size and shape of the ridge while also allowing formation of new vital bone. Although autogenous grafts possess all beneficial qualities of the ideal bone graft, they are associated with relatively high morbidity 5 and increased surgical time, and they lack evidence demonstrating their superior qualities over other options.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]5,6 A goal of ridge preservation is to maintain the overall size and shape of the ridge while also allowing formation of new vital bone. Although autogenous grafts possess all beneficial qualities of the ideal bone graft, they are associated with relatively high morbidity 5 and increased surgical time, and they lack evidence demonstrating their superior qualities over other options. 4 Bone particulate allograft is a commonly used material to predictably maintain alveolar ridge dimensions 7 while also providing a scaffold for new host bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…As patient morbidity is increasing with every surgery and aesthetic outcome in the anterior area is more and more compromised, a central clinical focus is on preventing bone loss after tooth extraction. Recent systematic reviews of alveolar socket preservation have concluded that various techniques, including bone graft/substitute implantation, can reduce bone loss after tooth extraction compared with spontaneous alveolar healing, but that some loss of alveolar ridge height and especially width seems unavoidable [23,40,41]. Under physiological conditions, osteoclasts are mainly responsible for the vertical and horizontal loss of alveolar bone in the area of the extraction socket [42].…”
Section: Discussionmentioning
confidence: 99%